Effect of Moringa oleifera stem extract on hydrogen peroxide-induced opacity of cultured mouse lens - Lei Qi; Yu Zhou; Weijie Li; Mali Zheng; Ruisheng Zhong; Xin Jin; Yuan Lin (BMC, 2019)
Abstract Background Moringa oleifera, also known as horseradish tree or drumstick tree, has strong antioxidant properties. In the present study, we investigated the potential effect of Moringa oleifera stem extract (MOSE) on cataract formation induced by oxidative stress in cultured mouse lenses. Methods Mouse lenses cultured in vitro were pretreated with MOSE (0.5 and 1 mg/mL) for 24 h. Then, 1 mM hydrogen peroxide was added, and mouse lenses were cultured for a further 24 h. The medium was then changed to normal culture medium. After 48 h, lens opacification, reactive oxygen species (ROS) generation, reduced glutathione (GSH) content, and activities of superoxide dismutase (SOD) and catalase (CAT) were measured in lens tissues. In addition, the protein expression of peroxisome proliferator-activated receptor alpha (PPARα), a nuclear receptor with potential benefits to improve vision-threatening eye diseases, was assayed. Results MOSE (1 mg/mL) alleviated lens opacification, reduced ROS generation, increased GSH content, and elevated SOD and CAT activities in cultured lenses. Moreover, MOSE upregulated the expressions of SOD, CAT, and PPARα. Conclusions This study showed that MOSE alleviates oxidative stress-induced cataract formation, and the mechanism of the effect is mainly related to its improvement of the endogenous antioxidant system in the lens.